Clinical effects of using a massage chair on stress measures in adults: A pilot randomized controlled trial - Ji Yeon Baek; Eunju Lee; Bora Gil; Hee-Won Jung; Il-Young Jang (Elsevier, 2022)
Objective: Since the clinical benefits of a massage chair have not been fully elucidated, we aimed to assess the effects of the long-term use of a massage chair on stress measures in adults. Design: Randomized controlled trial. Setting: Community.InterventionsIn total, 80 adults aged 50-75 years were randomly assigned to the intervention group (n=41) and control group (n=39). The intervention group used the massage chair twice a day for 6 months. The control group was educated about lifestyle modification. Main outcome measures: The primary outcome was the change in serum cortisol levels in the morning (8 a.m.) and afternoon (1 p.m.), and the secondary outcomes included changes in levels of dehydroepiandrosterone-sulfate (DHEA-S), serotonin, insulin-like growth factor, erythrocyte sedimentation rate, high sensitivity C-reactive protein, and natural killer cell activity, and results from a questionnaire on mood, cognition, and quality of life. Results: The use of the massage chair was associated with a decreasing trend in serum cortisol levels at 1 p.m. (-2.68 ug/dL, p = 0.059). Serum DHEA-S levels significantly decreased with the intervention (-9.66 ug/dL, p = 0.003). In addition, the perceived rate of depression and health status considerably improved following the intervention. Conclusions: Chronic stress in adults could be effectively managed using a massage chair.